Immediate Dental Implant Placement After Removal of Complex Odontoma - de Souza Batista, Fábio Roberto; de Souza Batista, Victor Eduardo; Vechiato-Filho, Aljomar José; Tieghi Neto, Victor; Figueira, Jéssica Araújo; Verri, Fellippo Ramos [UNESP] (Wolters Kluwer, 2017)
The aim of the authors was to report a clinical case about immediate implant placement after the removal of complex odontoma. A 35-year-old female patient presented to private service complaining about absence of lower right first premolar. The computed tomographic showed radiopaque attenuation, surrounded by a narrow radiolucency in the area of dental absence, suggesting a mineralized lesion. The surgical removal of lesion was performed by intraoral access with general anesthesia and the implant of 3.75 × 10 mm (Neodent) was placed with the aid of a surgical guide, following the drill sequence established by the manufacturer. No complications were observed after 1 year with the prosthetic rehabilitation.